Sociocultural analyses of Malaysia’s Orang Asli preschoolers and computers: a qualitative case study - Adam Assim, Mohd Ibrani Shahrimin; Yaccob, Yasmin; Mat Jusoh, Nurul Hidayu (Human Resource Management Academic Research Society, 2020)
This study examined the patterns of socioculturally appropriate social interactions of Malaysia’s Orang Asli children in an educational computer environment. Rogoff’s Sociocultural Theory and the three foci of analyses were utilized in this study. A multi-method case study design was employed to identify the patterns of socioculturally appropriate social interactions unique to the Malaysia’s Orang Asli preschool children in Selangor. Twelve preschool children were observed and interviewed using a semi-structured questionnaire. Seven dominant interaction patterns related to socioculturally appropriate social interactions of Orang Asli preschool children were examined. Factors facilitating and inhibiting the social interactions were identified using the application of Rogoff’s three foci of analyses and series of semi-structured interviews with Malaysian preschool teachers and Orang Asli preschool children. Rogoff’s Sociocultural Theory and the three foci of analyses may present a more and thorough view of indigenous children’s understanding of an educational computer environment.